2023
DOI: 10.3390/metabo13030394
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antibacterial, Anti-Inflammatory, and Antiproliferative Activity of Sorghum Lignin (Sorghum bicolor) Treated with Ultrasonic Pulses

Abstract: This investigation aimed to determine the effect of high-power ultrasonic pulses on the antioxidant, antibacterial, and antiproliferative activity of sorghum (Sorghum bicolor) lignin. A lignin yield of 7.35% was obtained using the organosolv method. Additionally, the best conditions of the ultrasonic pulses were optimized to obtain a more significant increase in antioxidant capacity, resulting in 10 min for all treatments, with amplitudes of 20% for DPPH and FRAP, 18% for ABTS, and 14% for total phenols. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These pigments have generated great interest in the pharmaceutical food industry due to their various health-beneficial properties, promoting pharmacological effects related to oxidative stress [13,18,19]. Previous studies have shown that phenolic extracts from beans [20], chickpea [21] and sorghum [22] present high antioxidant activity with erythroprotective properties [9]. However, the impact of ABO and RhD blood groups on the evaluation of the erythroprotective potential of fucoxanthin, β-Carotene, gallic acid, quercetin and ascorbic acid as therapeutic agents against oxidative stress has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These pigments have generated great interest in the pharmaceutical food industry due to their various health-beneficial properties, promoting pharmacological effects related to oxidative stress [13,18,19]. Previous studies have shown that phenolic extracts from beans [20], chickpea [21] and sorghum [22] present high antioxidant activity with erythroprotective properties [9]. However, the impact of ABO and RhD blood groups on the evaluation of the erythroprotective potential of fucoxanthin, β-Carotene, gallic acid, quercetin and ascorbic acid as therapeutic agents against oxidative stress has not been reported.…”
Section: Introductionmentioning
confidence: 99%